末次冰期以來亞熱帶季風的變化規律: 美國西部的湖泊研究(3/3) - 李紅春 (2006)
計畫編號:NSC95-2116-M006-001 執行機構:成功大學地球科學系（所） 研究期間:2006-08~2007-07 利用美國西部加州的Salton Basin的古湖泊做為研究系統，分析蘊藏在湖相沈積物石灰華(Tufa)中的地球化學資訊，重建北美季風和西風帶在末次冰期以來高解析度的變化。第一年和第二年的研究中，我們採集水樣、生物殼、石灰華樣品，進行了AMS 14C定年穩定同位素，鍶同位素，常量及微量元素濃度的測定。在第三年的研究中，主要進行資料和資料總結，撰寫論文，在會議上彙報成果。通過三年來所獲得的地球化學資訊，我們可以描述北美季風和西風帶在過去兩萬年對科羅拉多河流域和Salton Basin 的氣候影響。對比美西Great Basin和中國東部以及其他地區的古氣候記錄，討論季風系統內部以及與ITCZ和西風帶之間的互動關係。重要的成果和結論有：1)Salton Basin在過去的4萬年來就存在比現今Salton Sea還要大的湖泊，特別是從600年前到19500年前一直存在一個大湖(Lake Cahuilla)，這不僅對古氣候的研究起著重要作用，也對瞭解科羅拉多河流向、本區史前人類活動有著重要意義。2)鍶同位素表明科羅拉多河在過去的二萬年基本上與Salton Basin相連，直到西元1700前後才斷開。3)從湖相石灰華中氧碳同位素記錄，我們推測在末次冰期時，北美季風較弱，研究區受西風帶南移的影響，氣候由乾冷轉向濕冷。湖相石灰華氧碳同位素記錄了16.5千年時的Heirich-1事件和15.5千年時的"US Trans Wet"濕事件。在Bolling-Allerod和Younger Dryas時期，本區的氣候條件與冰芯記錄、以及中國大陸東部地區石筍記錄的反應有所不同。至少在Younger Dryas時期的前半部分，本區的氣候是以冷濕為主，可能是因為西風帶的強烈南移所造成。4)在全新世早中期，本區的氣候表現為濕熱，反應了北美季風的強烈增加。北美季風在4 千年左右強烈減弱，在6.2and 2.5千年時為很幹的時期。在中世紀暖期時，本區的氣候較濕，顯示夏季風的增強。5)在本研究中，我建立了一個湖泊體系的氧同位素穩態模式，來描述濕度和溫度對氧同位素的影響。建立了一個湖泊體系的鍶同位素模型，用於判斷水體的來源。這兩個模式近期發表在SCI期刊上，將有較大影響。在過去三年中，本人共發表論文16篇，其中第一作者(含通訊作者)SCI論文5篇，非第一作者SCI論文5篇。指導學生發表中文學術期刊文章5篇。在2007年發表了3篇第一作者SCI論文，其中2篇是本研究的直接成果。從2006年8月1號起，我與合作者一共送交17篇會議摘要。其中，我作為第一作者的國際會議摘要4篇。在進行這個3年計畫的過程中，本人主持國立成功大學地球科學系的穩定同位素實驗室，將該實驗室初步建成了國際一流的同類實驗室，成為南臺灣最先進、最完善的穩定同位素實驗室。 This is a 3-yr project for study of the climate history of southwest US, which will shed light on the variability and forcing factor of North American Monsoon. Using 18O, 13C, 87Sr/86Sr, Mg/Sr and Sr/Ca records on well-dated (AMS 14C) shoreline lake tufas from Salton Basin, California, we have reconstructed a high-resolution and detailed history of the climate and hydrology of Salton Basin and the C.R. drainage Basin over the past 20 ka. During the first year and the second year of this 3-yr project, we completed field investigation and sampling tasks, did a lot of and lab analyses, and made significant progress in term of data treatment, meeting presentations and journal publications. In the third year, our work focused on the treatment of data, discussion of results, comparison with other records and writing up papers. We have established a detailed chronology of lake history in Salton Basin by AMS-14C dating on lake deposits. Various geochemical analyses on water, tufa carbonate and fossil shell have been done for large numbers of samples. These results allow us to decipher climatic changes under the influences of the westerly and N. American monsoon during the past 20 kyrs. Our study focuses on identification of climatic shifts down to sub-centennial scales and of the effect of changing jet stream and ITCZ positions and monsoon strengths on the regional climate. From the abundant data results, we have obtained the following important progresses and conclusions update: 1) Salton Basin has been filled with lakes since at least ~40,000 years ago in late Pleistocene. The last lake cycle named Lake Cahuilla had existed between at least between 600 and 19500 yr BP dated by AMS 14C dates. The result is not only very 4 important for paleoclimate reconstruction, but also important for studies of Colorado River direction and pre-historic human activity in the region. 2) The Colorado River had been connected with the Salton Basin during the most duration of the past 20 ka, until 1700 AD based on the 87Sr/86Sr record. 3) The tufa deposits started earlier in the southwest part of the lake than the northwest part, reflecting evolution of the lake’s chemistry and history. 4) The 18O and 13C records of the tufas exhibit paleoclimates of Salton Basin as follows. A relatively dry climate was between 20-18 kyr BP, followed by a wet climate between 18-17 kyr BP. Decreasing P–E conditions from 17 to 16 kyr BP corresponded to Heinrich-1 event, whereas P–E increased ca.15.5 kyr BP during the “Trans US wet period”. From 15.2 to 11 kyr BP, the tufa record shows the Bølling-Ållerød interstadial and Younger Dryas events, but with different climate conditions shown in the Greenland ice cores. In the Salton Basin, the early part of YD was wet, perhaps due to the southward shift of the Westerlies. 5) Wet/warm early Holocene corresponding to the Maximum Effective Moisture period perhaps brought about by the strengthening of N. American Monsoon. Toward 2 kyr BP, the climate became dryer, apparently resulting from weakening of the monsoons especially around 6.2 and 2.5 kyr BP. A wet regime occurred in the basin during the MedievalWarm Period. 6) Between 1300 and 18000 yr BP, Lake Cahuilla level was above -24m a.s.l. which was at least 50m higher than modern Salton Sea. Between 1300 and 7000 yr BP, the lake stayed at the highest level —12m a.s.l. which was 87m higher than Salton Sea. After 1300 yr BP, the lake dropped its level rapidly and Salton Basin became a part of Sonora Desert. Human occupation on the lake shore below 12m a.s.l. should be after 1300 yr BP or before 7000 yr BP. 7) I have developed a mass balance model of stable oxygen isotope for a steady-state lake system, and used the 18O values in tufa samples to decipher variations of relative humidity in the Basin. I also established a mass balance model of Strontium isotopes for the lake system, which helped us to understand the source of input water and connection of Colorado River with the basin. These models are benefit to the community at large. In the 3-yr period, I have published 10 SCI papers. Amongst them, five are of my name as the first author or corresponding author. Other 6 peer-reviewed the papers 5 were published in Chinese journals. In the third year of the project, I have submitted 4 abstracts to international conferences. There are other 13 abstracts with my name submitted to national meetings. During the past three years, the most important accomplishment in my career is that I have built a state-of-art stable isotope lab in the department of earth sciences at the national Cheng-Kung University. This lab, with limited resources, becomes an analytical center of stable isotopes for scientists in Taiwan.